Trimetazidine improves angiogenesis and tissue perfusion in ischemic rat skeletal muscle - Pan, Yongting; Mai, Li; He, Wenkai; Yang, Xuqi; Wu, Enting; Zhao, Jiayuan; Liu, Bailiang; Li, Mingyan (Frontiers in Pharmacology, 2024)
Peripheral artery disease (PAD) is an increasingly common disease, causing significant complications for patients. Trimetazidine (TMZ) not only improves clinical symptoms in PAD patients but also facilitates angiogenesis in ischemic hind limbs. Our aim was to find the function of TMZ in promoting angiogenesis and tissue perfusion in ischemic rat skeletal muscle. The rats underwent femoral artery ligation (FAL) and then treated with TMZ and saline. Hematoxylin-eosin and Masson's trichrome stain in the ischemic gastrocnemius muscle to analyze muscle morphology and atrophy. To identify angiogenesis and the tissue perfusion, CD31 immunohistochemical staining and laser speckle contrast imaging was conducted. Additionally, hind limb motor ability was measured. Finally, qRT-PCR and Western blotting were used to statistically analyze the expression levels of HIF-1α and VEGF. Our study demonstrated significant enhancement in angiogenesis and tissue perfusion after FAL when treated with TMZ compared to the saline group. Histologically, it mitigates ischemia-induced muscle atrophy and inflammation, as well as reduces fibrosis progression in the TMZ group. Additionally, hind limb motor ability improved in rats treated with TMZ during motor experiments. It suggests that TMZ can promote angiogenesis and improve tissue perfusion in ischemic skeletal muscle of rats by activating the HIF-1α/VEGF signaling pathway. Additionally, it leads to significant improvement in ischemia-induced motor limitations in the hind limbs of rats.